Reflection group devices in university education as a mental health promotion strategy - Ghisiglieri, Francisco (2020)
University studies are crossed by a social environment that makes it difficult to meet others and joint reflection; a context that often tends to the isolation and removal of critical thinking. Faced with this, since 2013 we have developed a working device with workshops and reflection groups with students from Psychology Degree. These devices seek to develop feelings of permanence and belonging to the University, stimulate tolerance, respect, participation, social and institutional commitment, promoting the achievement of ethical and responsible professional subjectivity. In this paper we propose to qualitatively analyze the characteristics of the group ties that were generated within this intervention. To this end, we analyze the participant observation records made from 2013 to 2019. We find that these groups in university offer a prop up that is vitally important to go through the uncertainties inherent to entering the faculty, the vicissitudes of studies and vocational crises that may appear. With others, we find that students discover alternative ways to deal with discomfort and create possibilities that allow them to find a healthier way to deal with the challenges of studying.